Latino Cigarette Smoking Patterns by Gender in a US-National Sample. Issue 1 (25th August 2015) - Kristman-Valente, Allison N.; Flaherty, Brian P.
Abstract: Background: Latino smokers are a rising public health concern who experience elevated tobacco-related health disparities. Purpose: Additional information on Latino smoking is needed to inform screening and treatment. Analysis: Latent class analysis using smoking frequency, cigarette preferences, onset, smoking duration, cigarettes per day, and minutes to first cigarette was used to create multivariate latent smoking profiles for Latino men and women. Results: Final models found seven classes for Latinas and nine classes for Latinos. Despite a common finding in the literature that Latino smokers are more likely to be low-risk intermittent smokers, the majority of classes for both males and females described patterns of high-risk daily smoking. Gender variations in smoking classes were noted. Conclusions: Several markers of smoking risk were identified among both male and female Latino smokers, including long durations of smoking, daily smoking, and preference for specialty cigarettes, all factors associated with long-term health consequences.